Why Semioticians Love Vaižgantas, or the Never-ending Testing of the Method - Mačianskaitė, Loreta (Semiotika, 2021)
This research was inspired by the anniversaries of Algirdas Julius Greimas, Juozas Tumas-Vaižgantas and Kęstutis Nastopka that encouraged rethinking the relationship with tradition, while viewing it from several perspectives: biographical-cultural links, reception of classical literature, and history of Lithuanian semiotics. The paper reviews the works of semioticians’, analysing Vaižgantas’ oeuvre, attempting to find the trajectory of the evolving Lithuanian semiotic tradition in the most representative examples. It also presents a new interpretation of Vaižgantas’ novella, “Dėdės ir Dėdienės” (“Uncles and aunts”, 1929), while searching for the mythological reasons behind the motivations for its characters’ choices and referring to the arch-plot of Perkūnas-Velnias-Laumė. The entanglement of the planes of the hierogamy (the holy marriage) isotopy and the biblical one allows for interpreting this novella as a variation of the Exodus Myth. The problematics of parable discourse is exposed in considering the question of Vaižgantas’ semiotic originality.
Keywords: Vaižgantas; Greimas; Semiotics; parable; myth